The Din of Malcolm: Projections of Islam in France and the United Kingdom, 1964-1965 - Ambar, Saladin M. (Journal of Africana religions, 2015)
This article addresses the purpose and question of Malcolm X's (El-Hajj Malik El-Shabazz's) articulation of Islam during his travels to Europe in the last months of his life and its implications for Africana religions fifty years after his assassination. While there has been growing scholarly attention to the international dimension of Malcolm X's politics, there has been far less attention paid to the projections of his religious identity abroad; this is especially true for his time in Europe. By focusing on three speeches he delivered in Paris, Oxford, and London in context, I hope to illuminate how and why Malcolm X's Muslim identity in Europe has significance for both contemporary scholars and laypersons alikeinasmuch as his personal presentation of Islam reflected, at times, both a reluctance to make his faith central to his arguments, as well as an acceptance of sorts of the idea that religion had a place in the broader anticolonial and antiracist movements of his era.